Assessing grazing animal production systems on large Greek islands: A case study on the island of Crete - Hadjigeorgiou I.; Zervas G. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Greece has a long history of breeding sheep and goats utilizing the indigenous vegetation, under a system of free ranging or shepherded grazing, which in combination to some shepherds’ practices formed the present land cover and biodiversity. Islands present an interesting model for animal farming activity. The study area was the island of Crete in the South Aegean Sea. The land area covers some 825,000 ha and officialy holds a population of 600,000 inhabitants, while considerable numbers of sheep and goats (1,270,000 and 580,000 respectively) are raised. These animals produce 88,000 tonnes of sheep milk and 52,000 tonnes of goat milk, together with 14,300 tones of sheep and 6,600 tonnes of goat meat. Production systems applied in this island, were investigated and flocks were divided in semi-intensive and extensive. However, since pedoclimatic conditions vary widely, in order to advise grazing management rules in the different areas, a combination of National Statistics, CORINE and field data was used to define system dependence on local grazing resources. Subsequently grazing capacities were determined and advised to the local authorities together with management guidelines with the aim of maintaining the preserved areas under moderate grazing activity.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)